EVALUASI FUNGSI GINJAL BERDASARKAN FARMAKOKINETIK EKSKRESI PADA PASIEN HIPERTENSI DI INSTALASI RAWAT INAP RSUD CILINCING JAKARTA UTARA - Egy Octaviani; Fajar Amirulah; Dini Permata Sari; Rangki Astiani (Universitas 17 Agustus 1945 Jakarta, 2026)
Hypertension is a major risk factor for impaired renal function, which may progress to chronic kidney disease (CKD). This study aimed to evaluate renal function based on excretory pharmacokinetic parameters (urea, creatinine, and creatinine clearance) in hypertensive inpatients, and to assess the impact of patient characteristics and types of antihypertensive drugs on renal function decline. This observational analytic study with a cross-sectional design utilized secondary data from 100 medical records of hypertensive inpatients at RSUD Cilincing, North Jakarta, collected during March–April 2025. Most patients were classified in CKD stages 2–3a. The most frequently prescribed therapies were calcium channel blockers (CCBs) and angiotensin receptor blockers (ARBs). Chi-Square analysis revealed significant associations between renal function and gender, age, and CCB use (p < 0.05), while diuretic use was not significantly associated (p = 0.134). These findings highlight the importance of appropriate antihypertensive drug selection and regular renal monitoring to prevent CKD progression in hypertensive patients.